Legal Consequences of Divorce in Intermarriage on the Marital Property in the form of Land Proprietary Rights - Wiryani, Fifik; Anggraeny, Isdian; Kusuma Ayu, Isdiyana; ., Nurzakiah (KnE Social Sciences, 2024)
Intermarriage brings legal consequences to the assets in the marriage including the mixing of joint assets. Marital property, specifically, regarding land ownership rights in Indonesia causes a problem if there is a divorce. The joint assets in the form of ownership rights to the land must be shared between Indonesian Citizens and Foreign Citizens while Law Number 5 of 1960 concerning Basic Regulations -The Agrarian principle prohibits foreign nationals from owning property rights. This research aims to find out the position of Foreign Citizens regarding land ownership rights in Indonesian laws and regulations and the legal consequences of divorce on land ownership rights in mixed marriages. This research is normative legal research, the type of research used is research on legal systematics by taking inventory of laws and regulations governing land ownership rights in intermarriage, identifying problems, and analyzing them qualitatively. Keywords: intermarriage, land proprietary rights, divorce